Influence of multidrug resistant organisms on the outcome of diabetic foot infection. (May 2018) - Saltoglu, Nese; Ergonul, Onder; Tulek, Necla; Yemisen, Mucahit; Kadanali, Ayten; Karagoz, Gul; Batirel, Ayse; Ak, Oznur; Sonmezer, Cagla; Eraksoy, Haluk; Cagatay, Atahan; Surme, Serkan; et al.
Highlights: Among rehospitalized patients, methicillin resistant Staphylococcus infections was detected as the most common agent. Infections due to Klebsiella pneumonia have significantly higher fatality rates. Chronic heart diseases and the need for dialysis increase the risk of fatality. Abstract: Objectives: We described the clinical outcomes of the diabetic patients who had foot infections with multidrug resistant organisms. Methods: We included the patients with diabetic foot infections (DFI) from 19 centers, between May 2011 and December 2015. Infection was defined according to IDSA DFI guidelines. Patients with severe infection, complicated moderate infection were hospitalized. The patients were followed-up for 6 months after discharge. Results: In total, 791 patients with DFI were included, 531(67%) were male, median age was 62 (19–90). Severe infection was diagnosed in 85 (11%) patients. Osteomyelitis was diagnosed in 291(36.8%) patients. 536 microorganisms were isolated, the most common microorganisms were S. aureus (20%), P. aeruginosa (19%) and E. coli (12%). Methicillin resistance (MR) rate among Staphylococcus aureus isolates was 31%. Multidrug resistant bacteria were detected in 21% of P. aeruginosa isolates. ESBL (+) Gram negative bacteria (GNB) was detected in 38% of E. coli and Klebsiella isolates. Sixty three patients (8%) were re-hospitalized. Of the 791 patiens, 127 (16%) had major amputation, and 24 (3%) patients died. In multivariate analysis, significant predictors for fatality were; dialysis (OR: 8.3, CI: 1.82–38.15, p = 0.006), isolation of Klebsiella spp. (OR:7.7, CI: 1.24–47.96, p = 0.028), and chronic heart failure (OR: 3, CI: 1.01–9.04, p = 0.05). MR Staphylococcus was detected in 21% of the rehospitalized patients, as the most common microorganism (p < 0.001). Conclusion: Among rehospitalized patients, methicillin resistant Staphylococcus infections was detected as the most common agent, and Klebsiella spp. infections were found to be significantly associated with fatality.